Para além do escurinho do cinema: a representação do Nordeste em “O auto da compadecida" e "Deus e o diabo na terra do sol” - Santos, Kelvo de Almeida (2010)
This work analyzes how the Brazilian northeast is represented in two national films, located at different moments in Brazilian cinematography: Deus e o Diabo na Terra do Sol, belonging to Cinema Novo, directed by Glauber Rocha; and O Auto da Compadecida, directed by Guel Arraes from Pernambuco, a film that is part of the so-called Cinema de Retomada. The analysis tries to understand how the elements of the culture of the northeast region are treated in such films: the landscape, the religiosity, the mysticism and the characters that travel through this landscape: the bandit, the gunman, the killer, etc. The work also analyzes the historical construction of the regionalist discourse and the way in which the category “region” was born. This study also makes a didactic-historical examination of the emergence of Cinema Novo and Cinema de Retomada, focusing on the representation of the northeast in the films under analysis, as well as it analyses the elements that distance them from each other or bring them closer. Finally, the work concludes that the northeast is represented in an ambiguous way, sometimes highlighting its strength of power, sometimes relegating it to the space of mysticisms and backwardnesses, what, in this work, is called derogatory compliment.